THE INFLUENCE OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL COMMITMENT AND EMPLOYEE COMPETENCY ON JOB SATISFACTION THROUGH ORGANIZATIONAL BEHAVIOR AS INTERVENING VARIABLES IN PUBLIC WORKS AND SPACE ARRANGEMENTS IN THE KARIMUN DISTRICT COVID-19 ERA - Muliana, Heppy; Wibosono, Chablullah; Catrayasa, I Wayan; Gita Indrawan, Mohamad (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This research was conducted to determine the effect of organizational culture, organizational commitment and employee competence on job satisfaction through organizational behavior. The research method used is descriptive quantitative which provides an explanation of the description of organizational culture, organizational commitment and employee competence to work through organizational behavior. Sampling used proportionate random sampling technique with a sample of 80 respondents at the Public Works and Spatial Planning Office of Karimun Regency. The data collection technique used an instrument in the form of a questionnaire for analysis. The instrument was calibrated using item validity and reliability coefficients. Validity was tested using SEM-PLS analysis with the help of SmartPLS software.